Resisted sled sprint training to improve sprint performance: A systematic review - Petrakos, G.; Morin, J.-B.; Egan, B. (Sports Medicine, 2016)
Background: Based on recent findings regarding the mechanical determinants of sprint performance, resisted sled sprint (RSS) training may provide an effective tool for the improvement of sprint acceleration and maximal velocity. However, the volume and intensity for effective RSS training in different populations is unclear.